2013
DOI: 10.1111/jac.12048
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of A European Nuclear Collection of Brassica oleracea L. Landraces to Grow at High Temperatures

Abstract: Statistical models predict that global warming will have a negative impact in crop yields in the next decades. Especially vulnerable are winter crops such as kales or cabbages (Brassica oleracea L.). We evaluated the impact of high temperatures in morphological and biochemical traits of a B. oleracea core collection during early development. When grown at 30 °C, plants showed a reduction in chlorophyll content, early vigour and biomass compared with values observed on plants grown at 20 °C. Likewise, the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…Our model showed that both temperate and tropical regions are suitable for cabbage production. It makes sense that the annual mean temperature was the best predictor for the distribution, as high temperatures reduce crop establishment, yield and quality through inhibition of the photosystem II followed by decreases on the capacity of photosynthetic electron transportation (Díaz, De Haro, Muñoz, & Quiles, 2007;Rodríguez et al, 2014). However, the selection of cabbage populations with heat tolerance has already permitted their establishment in tropical areas (Rodríguez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our model showed that both temperate and tropical regions are suitable for cabbage production. It makes sense that the annual mean temperature was the best predictor for the distribution, as high temperatures reduce crop establishment, yield and quality through inhibition of the photosystem II followed by decreases on the capacity of photosynthetic electron transportation (Díaz, De Haro, Muñoz, & Quiles, 2007;Rodríguez et al, 2014). However, the selection of cabbage populations with heat tolerance has already permitted their establishment in tropical areas (Rodríguez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although higher temperature affects the flight A. monuste (> 30°C), flight only ceases entirely above 40°C (Nielsen & Nielsen, 1959). For cabbage, temperatures above 30°C cause a reduction in the rate of photosynthesis which also leads a decrease in growth (Díaz et al, 2007;Rodríguez et al, 2014). Furthermore, in the genus Brassica, wild species (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pepper HAESA-LIKE 1 (CaHSL1) gene, which encodes an HSL receptor-like protein kinase (RLK), is activated by CaWRKY40 or other HSFs, thus conferring thermotolerance under the HH condition by inducing the expression of genes encoding heat shock proteins (HSPs) [24]. In Brassica oleracea, an important vegetable crop, plant growth and development is negatively impacted by both HT and low temperature (LT) compared with 20 • C [25,26]. A number of genes responsive to short-term (2-4 h) HT conditions have been identified in cabbage (B. oleracea var.…”
Section: Introductionmentioning
confidence: 99%